Miniaturised Horst‐type Wilkinson power divider with simple layout. Issue 6 (1st March 2013) - Wang, X.; Sakagami, I.; Ito, N.; Mase, A.
Abstract : A Wilkinson power divider with an open‐circuited stub and extra‐transmission lines between two output ports is presented. Compared with the modified Wilkinson power divider presented by Horst, the proposed power divider has the advantages of less occupation area on a printed circuit board and simple layout, where the isolation resistor, one open‐circuited stub and extra‐transmission lines are constants. The experimental circuit shows good agreement with theoretical simulation.